Optimasi Pengelolaan Pengiriman Barang Melalui Aplikasi Monitoring Berbasis Web dengan PHP dan Bootstrap - Santoso, Miftah Faroq (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
This study aims to develop a web-based goods delivery monitoring application using PHP, MySQL, and Bootstrap to address the issues of limited visibility and real-time monitoring in the goods delivery process. The application provides real-time tracking features, shipment activity log recording, and a responsive interface, making it easily accessible across various devices. Bootstrap is employed to create a modern and user-friendly interface, while PHP and MySQL support the management of large and complex data. The research results indicate that this application successfully fills the gaps found in previous studies, particularly in terms of real-time monitoring and responsive design. With these features, the application can improve operational efficiency, reduce errors in the delivery process, and provide better transparency for users. Overall, this research contributes to the development of logistics information systems, especially in optimizing goods delivery management to be more efficient and user-friendly.